Optimizing HRM in Islamic Philanthropic Institutions: A Bibliometric Insight - Kholid, Kholid; Suyanto, Bagong; Lestari, Yetty Dwi (ZISWAF, 2024)
This study aims to analyze Human Resource Management (HRM) practices in Islamic philanthropic institutions, specifically focusing on zakat and waqf organizations. The research utilizes bibliometric analysis, sourcing data from the Scopus database and employing tools such as Biblioshiny and VOSviewer to map trends, identify gaps, and suggest improvements. The results show a lack of integration between modern HRM practices and Islamic ethical principles, as well as a shortage of empirical studies addressing the impact of HRM on organizational performance. Additionally, there is a lack of longitudinal research exploring long-term impacts, such as employee retention and organizational sustainability. The study recommends adopting strategic talent management, comprehensive employee development programs, and performance management systems that align Islamic values with modern HRM practices. The implications of this research are that these strategies are essential for improving organizational efficiency and sustainability, as well as creating a positive work environment rooted in Islamic ethics. Future research should explore these approaches to develop tailored HRM frameworks for Islamic philanthropic institutions.